Implementation of City Ordinance in a Highly Urbanized City: Inputs to Public Safety and Security - Gile, Wilzar L.; Plata, Nilmar P.; Anselmo, Charlie T.; Mosqueda, Riando D. (Future Science / FSH-PH Publications, 2025)
This study assessed the implementation of city ordinances in a highly urbanized city in the Philippines and their implications for public safety and security. A quantitative descriptive research design was employed, with data collected from 149 respondents, comprising police officers, barangay officials, and community residents, using a self-administered survey questionnaire. The findings revealed a strong consensus among the three groups, who rated the implementation of community service, issuance of violation receipts, filing of cases, and reporting procedures as